2020
DOI: 10.1016/j.srhc.2019.100464
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to utilization of antenatal care services in northern Uganda: A qualitative study

Abstract: Objective: Antenatal care (ANC) utilization remains a challenge in efforts to reduce maternal mortality and improve maternal health in Uganda. This study aimed to identify perceived barriers to utilization of ANC services in a rural post-conflict area in northern Uganda. Methods: A qualitative study using in-depth interviews and focus group discussions of seventeen participants (pregnant women, health workers and a traditional birth attendant). The study was informed through a phenomenological approach to capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 31 publications
1
31
0
1
Order By: Relevance
“…women feels that ANC is not necessary while 29% and 6.5% of the women said that they did not use the ANC services due to lack of support from husband and lack of support from health worker respectively. Similar study done by Uldbjerg C S et al, showed that the main perceived barriers to ANC utilization were identified as poor awareness among women, poor attitude of health workers, socio-cultural practices not being successfully aligned to ANC and lack of support from the husband, including difficulties in encouraging him to accompany to attend ANC [7].…”
Section: Discussionsupporting
confidence: 56%
“…women feels that ANC is not necessary while 29% and 6.5% of the women said that they did not use the ANC services due to lack of support from husband and lack of support from health worker respectively. Similar study done by Uldbjerg C S et al, showed that the main perceived barriers to ANC utilization were identified as poor awareness among women, poor attitude of health workers, socio-cultural practices not being successfully aligned to ANC and lack of support from the husband, including difficulties in encouraging him to accompany to attend ANC [7].…”
Section: Discussionsupporting
confidence: 56%
“…So to lower the perceived barrier, it is necessary to provide interventions in the form of health education in order to increase knowledge and awareness [31]. Culture and social environment can also be a perceived barrier for a person [32]. Intervention development programs are needed to lower the perceived barrier [33].…”
Section: Perceivedmentioning
confidence: 99%
“…Nisingizwe et al (2020) stated that perceived barriers reduced the use of antenatal care. According to Uldbjerg et al (2020), perceived barriers occurred due to lack of resources at health centers, poor attitudes of health care personnel, mismatches among ANCs, age of young or old mothers, procedures at the community health center, mandatory HIV testing and checking up. 11.…”
Section: The Effect Of Maternal Attitude Onmentioning
confidence: 99%
“…According to a study conducted by Uldbjerg et al (2020), the main barriers to the use of ANC that could be identified were unqualified services including poor behavior of health care personnel, socio-cultural practices that were not successfully harmonized with ANC, and low support from the husbands including difficulties in encouraging them to attend ANC. Poor knowledge and maternal attitudes of ANC will affect ANC visit practices.…”
Section: Introductionmentioning
confidence: 99%